Religion and Human Rights: The New Dimensions to the Society - Kaur, Paramjit (Journal of Advanced Research in Humanities and Social Sciences; Vol 8 No 3 (2021): Journal of Advanced Research in Humanities and Social Sciences, 2021)
There are various dimensions to the study in order to understand the religion and human rights. We need to analyse the various dimensions like religious, practical, narrative, philosophical, legal Institutional or social, emotional, phenomenological and materialistic dimensions etc. Attempts have been made to show the importance and futility of rights in the society. The greatest challenge of today is the interplay of nations and the clash of civilizations. From time immemorial, human beings have been associated with religion. Religious prophets, Gurus, saints and incarnations have played an important role in establishing human rights by teaching human beings to distinguish right and wrong through their teachings. In the light of man’s interrelationship with religion and in the light of sacred religious texts, human rights can be defined under different standards of society. This study seeks to consider the different dimensions of religion and human rights, the logical and non - logical beliefs and rituals within the needs of society. How to cite this article:  Kaur P. Religion and Human Rights: The New Dimensions to the Society. J Adv Res Humani Social Sci 2021; 8(3): 8-11. DOI: https://doi.org/10.24321/2349.2872.202103